Resolving between novelty and homology in the rapidly evolving phallus of Drosophila. Issue 2 (27th December 2021) - Rice, Gavin R.; David, Jean R.; Gompel, Nicolas; Yassin, Amir; Rebeiz, Mark
Abstract: The genitalia present some of the most rapidly evolving anatomical structures in the animal kingdom, possessing a variety of parts that can distinguish recently diverged species. In the Drosophila melanogaster group, the phallus is adorned with several processes, pointed outgrowths, that are similar in size and shape between species. However, the complex three‐dimensional nature of the phallus can obscure the exact connection points of each process. Previous descriptions based upon adult morphology have primarily assigned phallic processes by their approximate positions in the phallus and have remained largely agnostic regarding their homology relationships. In the absence of clearly identified homology, it can be challenging to model when each structure first evolved. Here, we employ a comparative developmental analysis of these processes in eight members of the melanogaster species group to precisely identify the tissue from which each process forms. Our results indicate that adult phallic processes arise from three pupal primordia in all species. We found that in some cases the same primordia generate homologous structures whereas in other cases, different primordia produce phenotypically similar but remarkably non‐homologous structures. This suggests that the same gene regulatory network may have been redeployed to different primordia to induce phenotypically similar traits. Our results highlight how traits diversify and can be redeployed, even at short evolutionary scales. Abstract : Establishing homology in complex and rapidly evolving structures can be challenging yet it is vital for evolutionary studies. We investigate the various phallic outgrowths found in the Drosophila melanogaste r species subgroup and trace whether they develop from the same or distinct tissues. We find that structures previously thought to be homologous are in fact produced from different tissues. Research Highlight: By incorporating developmental analysis, we find that genital structures previously identified as homologs are novel structures. This highlights how developmental analysis can help resolve contentious claims of homology.